Lipschutz Ulcer in A Virgin Woman: A Case Report - I Gusti Ayu Agung Elis Indira; Vanessa Vijayamurthy; Made Dwi Puspawati; Anak Agung Gde Putra Wiraguna (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Lipschutz ulcer, also known as vulvae acutum ulcer, is an acute ulcer in the vulva. The aetiology and pathogenesis of Lipschutz ulcer are unclear, but it is known to be associated with infectious diseases such as Mycoplasma infection, paratyphoid fever, influenza A, and most infections with Epstein-Barr virus (EBV). This ulcer appears in adolescent females aged 14–20 years old, with 70% of cases occurring in virgin women. Purpose: To review the causes of non-Sexually Transmitted Diseases (STD) ulcers, so clinicians can establish an accurate diagnosis and rational therapy; therefore, minimizing the psychological impact on the patient due to possible misdiagnosis of STD-induced ulcer. Case: A painful wound in the genital area of a 20-year-old virgin woman. She was diagnosed with Lipshutz ulcer and vulvovaginal candidiasis based on the anamnesis, physical examination, and laboratory examination obtained from vaginal discharge using potassium hydroxide, Gram staining, and blood test to exclude genital ulcer caused by the sexually transmitted agent. A blood test was taken, including the serological tests for syphilis and genital herpes. Tests for EBV were also performed. The patient was treated only with single-dose fluconazole 150 mg orally and saline compress on the ulcer. Genital ulcer and vaginal discharge improved one week after treatment. Discussion:  Lipshutz ulcer management is symptomatic, usually self-limiting, and disappears spontaneously within 1–2 weeks without recurrences. It can also occur as a single lesion with possible coinfection of other agents, for example, candidiasis, which in this case, requires treatment of comorbidities. Hygiene factors play an essential role in preventing occurrence of the secondary infection and further development of the disease. Conclusion: The diagnosis of Lipshutz ulcer is mainly based on clinical manifestation after excluding several possible ulcers that can affect the genital area, including sexually transmitted infections.